D-Serine Released by Astrocytes in Brainstem Regulates Breathing Response to co2 Levels - Eugenin-Leon, J; Llona-Rodriguez, I; Zuniga-Navarro, G; Beltran-Castillo, S; Contreras-Arredondo, R; Olivares-Arce, M (Nature Publishing Group, 2017)
Central chemoreception is essential for adjusting breathing to physiological demands, and for maintaining CO2 and pH homeostasis in the brain. CO2-induced ATP release from brainstem astrocytes stimulates breathing. NMDA receptor (NMDAR) antagonism reduces the CO2-induced hyperventilation by unknown mechanisms. Here we show that astrocytes in the mouse caudal medullary brainstem can synthesize, store, and release d-serine, an agonist for the glycine-binding site of the NMDAR, in response to elevated CO2 levels. We show that systemic and raphe nucleus d-serine administration to awake, unrestrained mice increases the respiratory frequency. Application of d-serine to brainstem slices also increases respiratory frequency, which was prevented by NMDAR blockade. Inhibition of d-serine synthesis, enzymatic degradation of d-serine, or the sodium fluoroacetate-induced impairment of astrocyte functions decrease the basal respiratory frequency and the CO2-induced respiratory response in vivo and in vitro. Our findings suggest that astrocytic release of d-serine may account for the glutamatergic contribution to central chemoreception. © 2017 The Author(s).